Improving Mental Health of Adolescents Through the Practice of Prayer - Nahuda Nahuda; Dede Rosyada; Muhammad Farid Hamzens; Dina Rahma Fadlilah; Herwina Bahar (Indonesian Journal of Islam and Public Health, 2022)
In fact, many Muslims do not know how powerful the benefits of prayer are, especially for their health, namely mental health. Prayer activities that are always carried out on an ongoing basis are a medium to restore and get the peace and tranquility of the soul. There is a period when adolescents will experience vulnerable mental changes. Therefore, the dimensions of education and the practice of praying in daily life, it is a determining factors in forming a good Muslim personality for mental health in adolescents. The method in this study uses a literature review method. The search for articles is done by searching on the google search engine with the keywords mental health and the practice of prayer. This writing has the aim of knowing the improvement of mental health through the practice of prayer. The search results from the study found that mental health can be improved through the practice of prayer. Research conducted by Umri Biologi and Anisa Maya (2020) discusses prayer as a means of solving mental health problems. The results of the study said that prayer is an activity that raises the spiritual status of adolescents so that they can control stress in adolescents. Based on the discussion of this literature review, it can be concluded that there is an increase in mental health through the practice of Islamic worship, namely prayer.